Zinc in the Monoaminergic Theory of Depression: Its Relationship to Neural Plasticity - Cui, R.; Radziwoń-Zaleska, Maria; Nowak, Gabriel; Wlaź, Piotr; Doboszewska, Urszula; Młyniec, Katarzyna (Neural plasticity, 2017)
Preclinical and clinical studies have demonstrated that zinc possesses antidepressant properties and that it may augment the therapy with conventional, that is, monoamine-based, antidepressants. In this review we aim to discuss the role of zinc in the pathophysiology and treatment of depression with regard to the monoamine hypothesis of the disease. Particular attention will be paid to the recently described zinc-sensing GPR39 receptor as well as aspects of zinc deficiency. Furthermore, an attempt will be made to give a possible explanation of the mechanisms by which zinc interacts with the monoamine system in the context of depression and neural plasticity.